#TITLE_ALTERNATIVE# - DELTA, RISEN
API 5L-X52 is a pipe with material classified as one of the high strength low alloy steel and often used for oil and gas distribution. The consequence of thermal cycle by fast heating and cooling on welding steel results the un-uniformity on microstructure and mechanical properties. Heat treatment is a procedure to increase the endurance against brittle fracture after welding, by homogenizing the hardness at weld metal, HAZ, base metal zone, and decreasing residual stress. In this research, the experiment will be focused on the effect of heat treatment temperature increase 200 degrees C, 300 degrees C, 400 degrees C, and 500 degrees C for 30 minutes on weld area hardness and microstructure. Material of the pipe used is API 5L-X52 weld area with 12.4 mm welding thickness and 9.8 mm base metal thickness. Sampling acceptance criteria compared with API and ASM standard will be obtained based on the result of visual & dimensional test, and as received tensile test on weld area. Chemical composition test, hardness test, and metallographic is conducted to observe the phases to the effect of hardness distribution on steel. Based on the experiment, sample is in a good condition to be processed by heat treatment since there is no offset of plates, slag inclusion, Lack of Fusion (LOF) & Lack of Penetration (LOP), undercut and overlap. The increase of heat treatment temperature on API 5L-X52 steel will decrease hardness distribution from as received until 500 degrees C because of the increase of grain size. The hardness distribution increases from base metal until weld metal. Hardness homogenization occurred at 500 degrees C with hardness value between 170-200 HVN. Heat treatment products fine ferrite phase on base metal, coarse ferrite and acicular ferrite on HAZ zone, acicular ferrite and polygonal ferrite phase on weld metal. Since martensite phase is not found on the sample and the hardness is below 240 HVN, the sample is not susceptible of cold cracking which is brittleness because of the high percentage martensite and hydrogen on HAZ. The result of tensile test on as received welding zone shows that ?UTS=653.33 MPa, indicates that the test result is still on API standard.